Comparison of Ga-68-Labeled Fusarinine C-Based Multivalent RGD Conjugates and [(68)Ga]NODAGA-RGD-In Vivo Imaging Studies in Human Xenograft Tumors - Zhai, Chuangyan; Franssen, Gerben M; Petrik, Milos; Laverman, Peter; Summer, Dominik; Rangger, Christine; Haubner, Roland; Haas, Hubertus; Decristoforo, Clemens (Molecular imaging and biology, 2016)
PURPOSE: Multimeric arginine-glycine-aspartic acid (RGD) peptides have advantages for imaging integrin αvβ3 expression. Here, we compared the in vitro and in vivo behavior of three different Ga-68-labeled multimeric Fusarinine C-RGD (FSC-RGD) conjugates, whereby RGD was coupled directly, via a succinic acid or PEG linker (FSC(RGDfE)3, FSC(succ-RGD)3, FSC(Mal-RGD)3). The positron emission tomography/X-ray computed tomography (PET/CT) imaging properties were further compared using [(68)Ga]FSC(succ-RGD)3 with the monomeric [(68)Ga]NODAGA-RGD in a murine tumor model. PROCEDURE: FSC-RGD conjugates were labeled with Ga-68, and stability properties were studied. For in vitro characterization, the partition coefficient, integrin αvβ3 binding affinity, and cell uptake were determined. To characterize the in vivo properties, biodistribution studies and microPET/CT were carried out using mice bearing either human M21/M21-L melanoma or human U87MG glioblastoma tumor xenografts. RESULTS: All FSC-RGD conjugates were quantitatively labeled with Ga-68 within 10 min at RT. The [(68)Ga]FSC-RGD conjugates exhibited high stability and hydrophilic character, with only minor differences between the different conjugates. In vitro and in vivo studies showed enhanced integrin αvβ3 binding affinity, receptor-selective tumor uptake, and rapid renal excretion resulting in good imaging properties. CONCLUSIONS: The type of linker between FSC and RGD had no pronounced effect on targeting properties of [(68)Ga]FSC-RGD trimers. In particular, [(68)Ga]FSC(succ-RGD)3 exhibited improved properties compared to [(68)Ga]NODAGA-RGD, making it an alternative for imaging integrin αvβ3 expression.
Keywords: železité sloučeniny; tkáňová distribuce; zobrazování trojrozměrné; Positron Emission Tomography Computed Tomography; Fusarinine C; Endocytosis; Cell Line, Tumor; Ferric Compounds; Tissue Distribution; Integrins; radioizotopy galia; Radiopharmaceuticals; Xenograft Model Antitumor Assays; myši nahé; myši inbrední BALB C; Acetates; Imaging, Three-Dimensional; Hydroxamic Acids; endocytóza; Mice, Inbred BALB C; Oligopeptides; xenogenní modely - testy protinádorové aktivity; Melanoma; radiofarmaka; Animals; acetáty; lidé; ženské pohlaví; Gallium Radioisotopes; Heterocyclic Compounds, 1-Ring; Humans; Gallium-68; zvířata; Positron emission tomography (PET); kyseliny hydroxamové; PET/CT; RGD peptides; Mice, Nude; nádorové buněčné linie; Female; melanom; oligopeptidy; heterocyklické sloučeniny monocyklické